SHORTENING THE DURATION OF THE SECOND STAGE OF LABOR AND INCREASING COMFORT WITH ESA CHAIR - Mardiani, Dita Eka; Sapia, Noni; Lestari, Meti Widiya; Rismawati, Sariestya; Purnamasari, Wiwin Mintarsih; Mulyani, Nunung; Nurcahyani, Lia; Tajmiati, Atit; Badriah, Siti; Sofie, Muhamad (IAKMI South Tangerang Branch, 2025)
Background: The duration of labor is an important indicator of maternal and infant safety. The success and length of labor is influenced by birthing position. The ESA chair is designed to facilitate an upright position during labor, which, in theory, speeds up the birth process and increases maternal comfort. Objective: to analyze the comparison of the duration of mothers using ESA chairs and delivery beds at independent midwives in Tasikmalaya city. Method: This study used a quasi-experimental approach with a two-group-posttest-only design, namely interventions in the group of mothers giving birth using ESA chairs and the group of mothers giving birth using delivery beds. The sampling technique used a total of 24 respondents. Data analysis used the Mann-Whitney test. Results: The results of the analysis showed that the duration of labor between the two groups showed that the average duration of labor in the ESA Chair group (34.23) was significantly faster than the average duration of labor in the “Delivery Bed” group (51.45). The results of statistical analysis using the Mann-Whitney test showed a p-value of 0.000. Conclusion: ESA chairs are more effective than delivery beds in shortening the duration of labor in mothers.